Implementation Information System for Health Faculty Student Admissions in Measuring the Effectiveness of Digital Marketing on the Attractiveness of the Selection of Health Faculties - Maria Septijantini Alie; M.Budi Hartanto; Umar Bakti (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
New student admissions for the health faculties of Indonesian partner universities have indeed used the website at pmb.umitra.ac.id, added features in the registration of new students that have the effect of digital marketing applied to increase attractiveness to the selection of health faculties. Therefore, researchers and the team are trying to reactivate the function of the registration website, and implement the optimization of the online registration, and help organize new student admissions at the website-based health faculty, as well as to measure the effectiveness of digital marketing on the attractiveness of choosing specializations in the health faculty whose framework is made integrated with new student registration website at the health faculty. Researchers and the team used quantitative descriptive methods and data collection techniques were carried out by literature studies and field research. It is hoped that this will increase the number of students enrolled interested in the faculty of health and the effectiveness of digital marketing at Indonesian partner universities. Can be a solution in increasing the number of new students at the health faculties of Indonesian partner universities.